Implementación de protocolos de seguridad para la red VoIP del hospital Isidro Ayora de Loja. - Calderón Ordoñez, Cristian Leonardo (2015)
The present work of career end, it is guided to carry out an analysis of the threats that affect to the nets taking advantage of any weakness of the net, (VoIP), for to do this carried out it a scanner, with the purpose of finding the teams that conform it, as well as the extensions that supports (PBX), using computer, denominated (sniffers) tools, which determine what weaknesses they exist at the moment in the net, to achieve this objective, one worked on a scenario of tests, where two connected machines to the (PBX), communicate to each other and a third intruding machine that has been able to enter to the net it captures the established communication among those attacked, being able this way to record the calls that settle down among the two victims, using the eavesdropping technique, which has as objective, to intercept data in a transmission in a not authorized way. For the development of the present project, the following methodologies were used: (OSSTMM), to be one of those most used ones, for the search and verification of vulnerabilities, in nets that have an Internet connection, together with the distribution Kali Linux, to be an operating system that has a lot of tools, specialized for tests of security or what is known as ethical hacking, likewise, for the analysis and management of risks, the methodology (OCTAVE) was used, with the purpose of classifying the level of risks, according to the vulnerabilities found in the telephony net, (IP),of Isidro Agora’s Hospital of Loja city. To counteract the vulnerabilities of more risk, found in the net of (VoIP), it was carried out an analysis of the different protocols of security, like they are (SSL / TLS) and (IPsec), with the purpose of choosing the protocol with the best characteristics and that they adapt to the configuration of the net (VoIP), to hide the opposing vulnerabilities, Finally it put into operation the protocol of security (SSL / TLS), to be the one that better it adapts to the functionality of the net and it is supported by the servant of (VoIP), in conclusion, they were carried out the tests of the configuration, being successful because the covered all the vulnerabilities classified with the highest risk.